Integrating Memorised Quranic Verses With Aqli Knowledge Model In Kolej Genius Insan - Ahmad Bazli Bin Ahmad Hilmi
Integrating naqli and aqli knowledge (INAQ) is compulsory in every subject at Kolej GENIUS Insan (KGI), and the implementation of INAQ also involves Quranic education. However, specific guidelines in integrating memorised Quranic verses with aqli knowledge have not been highlighted. This study aims to develop a model for integrating memorised Quranic verses with aqli knowledge based on the discipline of Quranic exegesis for the use of secondary students at KGI. This study used the Design and Developmental Research (DDR) approach founded by Richey and Klein (2007), which has three phases: needs analysis, design and development, and usability evaluation. For the need analysis, a survey using interviews was conducted among Quran teachers, alumni, and students of KGI to know the implementation of integrating memorised Quranic verses with the aqli knowledge. The second phase has been divided into two subphases: 1. Subphase of designing model based on the literature review and the Focus Group Discussion (FGD) method involving seven experts 2. Subphase of developing model using the Fuzzy Delphi Method (FDM) approach involving twelve experts. The prototype model for integrating memorised Quranic verses with aqli knowledge is the result of this phase. In the third phase, Nominal Group Technique (NGT) involving nine experts was used to assess the model’s usability. The result of this study is a model of integrating memorised Quranic verses with aqli knowledge consisting of five components, five phases, eight subphases, and sixty-eight elements. The model provides guidelines to Quran teachers and students of KGI in integrating memorised Quranic verses with aqli knowledge.